Pendampingan Penyaluran Dana Ziswaf Lembaga Kotak Amal Indonesia pada Program Roadshow Sekolah Bakat di Desa Blimbing, Mojo, Kediri - Hakim, Lukman; Asghori, Ahmad Azis; Khusnun, Moch Saiful; Zunaidi, Arif; Yanto, Rafi Dwi (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The country of Indonesia is predominantly Muslim. Zizwaf is a means of distributing wealth in the Islamic economic system. The potential for collecting Ziswaf funds is very high. Seeing the potential for so many Ziswaf funds, they need to be managed properly so that they can develop the community’s economy. In the Kediri district, there is an Amil institution called Kotakamal Indonesia (KAI), which has various innovative programs starting with collection and distribution. At Kotakamal Indonesia, there are many programs for channeling ziswaf funds, one of which is the Talent School Roadshow program. The activity method uses a structured implementation method. The Indonesian charity box has the goal of improving the standard of living of disadvantaged people in the economic or educational fields. The Indonesian Kotamal Institution not only distributes ziswaf funds but also teaches several talents to be taught to orphans and the poor. Therefore, the Talent School Roadshow program will be carried out by the Kotamal Indonesia institution.